English Language Screening for Scientiﬁc Staff at Delft University of Technology - Klaassen, Renate G.; Bos, Madeleine (HERMES - Journal of Language and Communication in Business, 2010)
Delft University of Technology (DUT) screened her (non-native English) scientiﬁc staff on their level of English proﬁciency in the academic year of 2006/2007. In this paper this large scale operation, involving planning, policy decisions, assessment means, advice and training are discussed. Since 2005 all the master programmes at DUT have been taught in English and since 3 years ago DUT has been an ofﬁcially bilingual university with around 5,500 master students and 1,100 international students in the year 2008. Therefore, results are framed against the background of becoming an international university.